INVERSE DISTANCE WEIGHTED METHODS IN GROUNDWATER MODELLING PONJONG AREA, GUNUNG KIDUL REGENCY, SPECIAL REGION OF YOGYAKARTA, INDONESIA - Sari, Avellyn Shinthya (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2024)
Groundwater modeling is needed to display the underground dimensions of groundwater. The Inverse Distance Weighting (IDW) technique is the choice as the basis for groundwater model analysis because the analysis using this technique remains accurate even though it only uses a few sample points. The groundwater model in Sidorejo Village, Ponjong District, Gunungkidul Regency, Yogyakarta Special Region has a water thickness of between 4.5 – 13.85 meters. With a pore aquifer system, because based on data from field observations and interpretation of geological maps, Sidorejo village, Ponjong District, Gunungkidul Regency, Yogyakarta Special Region is included in the Wonosari formation with geological structures in the form of limestone, reef, calcarenite, calcarenite tuffan. As for the direction of groundwater flow to the west, following the slope of the slope found at the study site. While the results of groundwater quality analysis using the Inverse Distance Weighting (IDW) technique by testing several parameters including the degree of acidity (pH), electrical conductivity (DHL), Total Disolved Solid (TDS), iron (Fe), calcium (Ca) , magnesium (Mg), and calcium carbonate (CaCO3) it can be concluded that all test well samples indicated no contamination because all test parameters were still within normal limits.